Advances in Meat Research 1985
DOI: 10.1007/978-94-011-5939-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electrical Stimulation for Hot Boning of Meat

Abstract: With ever-increasing processing costs, the meat industry is being forced to look into new and innovative processing methods. The efficiency of marketing meat and moving it to the consumer must be increased. The meat industry must face these new challenges and demands in order to survIve. Over the past two decades, the meat industry has dramatically shifted its manner of distributing meat, from shipping beef to retail stores in carcass form to shipping beef to retail stores in the form of vacuum packaged primal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Many studies have been conducted on muscle biology regarding negative characteristics of prerigor muscles compared to postrigor ones. Prerigor beef is prone to "cold shortening" during rapid chilling, resulting in tougher muscle (Cross and Seideman, 1985). Since hot boning occurs before glycolysis is fully completed, prerigor meat still has a high pH with good ability for extracting myofibrillar protein and stabilizing fat as well as good water-holding ability for further processing (Claus and Sørheim, 2006).…”
Section: Healthier Meat Productsmentioning
confidence: 99%
“…Many studies have been conducted on muscle biology regarding negative characteristics of prerigor muscles compared to postrigor ones. Prerigor beef is prone to "cold shortening" during rapid chilling, resulting in tougher muscle (Cross and Seideman, 1985). Since hot boning occurs before glycolysis is fully completed, prerigor meat still has a high pH with good ability for extracting myofibrillar protein and stabilizing fat as well as good water-holding ability for further processing (Claus and Sørheim, 2006).…”
Section: Healthier Meat Productsmentioning
confidence: 99%
“…The post slaughter treatment carcass ES is one of the major interventions adopted in the meat industry for enhancing meat quality traits (Adeyemi et al, 2014). Cross et al (1985) reported that application of ES of carcasses bring significant effect on the aging periods saving and economic feasibility through improvement of meat tenderness. ES categorized into low voltage that is applied ranges from 20 to 120 V, or high voltage that is greater than 120 V. Moreover, an approach to stimulation had been developed in Australia based on medium voltages which were favoured over the traditional high voltage systems.…”
Section: Introductionmentioning
confidence: 99%
“…ELECTRICAL STIMULATION (ES) OF A BEEF CARCASS INCREASES the rates at which pH drops and glycogen levels decline. Because ES and hot boning may markedly affect processing, economics, and tenderness of meat, both treatments have been the subject of several studies (Cross and Seideman 1985). ES has the advantages of stabilizing color and increasing tenderness of meat (Devine et al, 1984;Chrystall and Devine, 1985;Uytterhaegen et al, 1992;Ho et al, 1996).…”
Section: Introductionmentioning
confidence: 99%